The Influence of Productive Asset Quality, Loan to Deposit Ratio, Non Performing Loan, and Operating Expenses to Operating Income on Profit with Capital Adequacy Ratio as Moderating Variable in Indonesian Banking - Hendro Sasongko; Nancy Yusnita (Jurnal Manajemen dan Keuangan, 2023)
Banking has an important role in the economy and has a function as an agent of trust, agent of development, and agent of services. In creating a healthy banking system, Bank Indonesia issued a program to strengthen national banking to strengthen capital in order to improve the ability of banks to manage business and risk. The purpose of this study was to analyze the effect of earning asset quality, loan to deposit ratio, non-performing loans, and operating expenses on operating profit with the capital adequacy ratio as a moderating variable in Indonesian banking. The sample selection was carried out by purposive sampling method, namely the 10 largest banks in Indonesia. The model estimation analysis method is done by panel data regression analysis. The results showed that the CAR variable as an intervention variable succeeded in increasing the effect of earning asset quality, loan to deposit ratio, non-performing loans, and expenses to operating income on return on assets